2012
DOI: 10.1371/journal.pone.0045139
|View full text |Cite
|
Sign up to set email alerts
|

RpaA Regulates the Accumulation of Monomeric Photosystem I and PsbA under High Light Conditions in Synechocystis sp. PCC 6803

Abstract: The response regulator RpaA was examined by targeted mutagenesis under high light conditions in Synechocystis sp. PCC 6803. A significant reduction in chlorophyll fluorescence from photosystem I at 77 K was observed in the RpaA mutant cells under high light conditions. Interestingly, the chlorophyll fluorescence emission from the photosystem I trimers at 77 K are similar to that of the wild type, while the chlorophyll fluorescence from the photosystem I monomers was at a much lower level in the mutant than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
3
12
0
1
Order By: Relevance
“…As reported from Majeed et al . (), ∆ rpaA displays a reduced phycocyanin (628 nm) to chlorophyll (680 nm) ratio compared to the WT, which is comparable to the phenotype of the ∆ rpaA strain, constructed in our study. The entire absorbance spectrum of ∆ rpaA /FLAG‐ rpaA resembles the WT spectrum, confirming the complementation of the ∆ rpaA phenotype by FLAG‐RpaA (Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As reported from Majeed et al . (), ∆ rpaA displays a reduced phycocyanin (628 nm) to chlorophyll (680 nm) ratio compared to the WT, which is comparable to the phenotype of the ∆ rpaA strain, constructed in our study. The entire absorbance spectrum of ∆ rpaA /FLAG‐ rpaA resembles the WT spectrum, confirming the complementation of the ∆ rpaA phenotype by FLAG‐RpaA (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Majeed et al . () reported a specific effect of rpaA deletion on photosynthetic complexes in high light. However, these studies did not analyze the behavior of the mutant in a light‐dark cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highlight acclimation is achieved by the interplay of transcriptional regulation by transcription factors (gray lines), s-factors (not included in the model), and posttranscriptional regulation by PsrR1 (blue lines). mechanism (Majeed et al, 2012). The transcriptional regulator PedR activates the expression of chlN, chlB, and chlL mRNAs (Nakamura and Hihara, 2006), which encode subunits of the lightindependent protochlorophyllide reductase under low-light conditions.…”
Section: Role Of Psrr1 In the High-light Responsementioning
confidence: 99%
“…Two proteins related to bacterial two-component signal transduction, Sll1871 of a HepK two-component system sensory histidine kinase and Slr0115 of a response regulator, were down-regulated in the ⌬sll0794 mutant. In the previous study, it has been found that Slr0115 regulates the accumulation of the monomeric photosystem I and the D1 protein under high light stress conditions (54).…”
Section: Fig 3 Reproducibility Between Biological Replicatesmentioning
confidence: 95%